2022
DOI: 10.3389/fphar.2022.831791
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Evaluation of Sdox, a Promising H2S-Releasing Doxorubicin for the Treatment of Chemoresistant Tumors

Abstract: Sdox is a hydrogen sulfide (H2S)-releasing doxorubicin effective in P-glycoprotein-overexpressing/doxorubicin-resistant tumor models and not cytotoxic, as the parental drug, in H9c2 cardiomyocytes. The aim of this study was the assessment of Sdox drug-like features and its absorption, distribution, metabolism, and excretion (ADME)/toxicity properties, by a multi- and transdisciplinary in silico, in vitro, and in vivo approach. Doxorubicin was used as the reference compound. The in silico profiling suggested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…Moreover, its biological activity strongly depends on its concentration; generally speaking, at a high concentration, H 2 S becomes cytotoxic, while at lower concentration, it can have explicit beneficial effects. In previous studies, the same authors have not observed any notable H 2 S-related toxic effects of H 2 S-DOXO [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, its biological activity strongly depends on its concentration; generally speaking, at a high concentration, H 2 S becomes cytotoxic, while at lower concentration, it can have explicit beneficial effects. In previous studies, the same authors have not observed any notable H 2 S-related toxic effects of H 2 S-DOXO [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 95%